Do Retirement Savings Increase in Response to Information About Retirement and Expected Pensions? - Mathias Dolls; Philipp Dörrenberg; Andreas Peichl; Holger Stichnoth (Center for Economic Studies and ifo Institute (CESifo), 2018)
How can retirement savings be increased? We explore a unique policy change in the context of the German pension system to study this question. As of 2005 (with a phase-in period between 2002-04), the German pension administration started to send out annual letters providing detailed and comprehensible information about the pension system and individual expected public pension payments. This reform did not change the level of pensions, but only provided information to individuals about their expected pension payments. Using German tax return data, we exploit an age discontinuity to identify the effect of these letters on the behavior of individuals. We find an increase in tax-deductible private retirement savings and provide evidence that this is not due to a crowding-out of other forms of savings. We also show that labor earnings, i.e. the most direct way to increase public pensions, increase after receiving the letter.
Keywords: H55; H24; D14; 330; pensions; savings; information letters; earnings